2018
DOI: 10.14791/btrt.2018.6.e1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Evaluation of Neurological Assessment of the Neuro-Oncology Scale in Glioblastoma Patients

Abstract: BackgroundThe aims of this study were to investigate the role of the Neurological Assessment of Neuro-Oncology (NANO) scale in predicting the prognosis of patients with glioblastoma, and compare these results to predicted data of the Karnofsky Performance Scale (KPS), and Eastern Cooperative Oncology Group (ECOG)/World Health Organization (WHO) performance status. Additionally, we examined other prognostic factors in glioblastoma patients.MethodsThe medical records of 76 patients with a new diagnosis of histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…ROC Curve Analysis for (A) KPS and (B) NANO scale before surgery towards favorable outcome categorize NANO scale as low 0-6 and high 7-23) has the sensitivity of 81.1% and specificity of 60%. These findings differ from previous study (Lee et al, 2018). For high KPS they obtain a range of 80-100, whereas for NANO Scale low score is 0-7.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…ROC Curve Analysis for (A) KPS and (B) NANO scale before surgery towards favorable outcome categorize NANO scale as low 0-6 and high 7-23) has the sensitivity of 81.1% and specificity of 60%. These findings differ from previous study (Lee et al, 2018). For high KPS they obtain a range of 80-100, whereas for NANO Scale low score is 0-7.…”
Section: Discussioncontrasting
confidence: 99%
“…These performance scales were functioned as a scale parameter in assessing patients' performance pre-treatment, to analyse their overall survival. It was found that performance status estimated by the NANO scale was significantly associated with overall survival, and showed to be a more powerful method to predict the prognosis of glioblastoma than the KPS, during both initial diagnosis and disease progression (Lee et al, 2018). However, not many studies assessed the fluctuations in functional scale during the progression of the disease, nor used a functional scale improvement as a favourable outcome.…”
Section: Karnofsky Performance Scale and Neurological Assessment Of Nmentioning
confidence: 99%
“…A low preoperative performance and functional status is often perceived to confer poor prognosis in GBM (Chambless et al, 2015; Smedley et al, 2018). Its predictability of survival length, however, continues to be unreliable (Lee et al, 2018). We posit that the missing association between neurologic deficit and survival length, within our cohort and across the wider GBM population, is due to the need to incorporate a combination of multiple clinical attributes to accurately predict patient outcome.…”
Section: Discussionmentioning
confidence: 99%
“…GBM patients typically present a spectrum of generalized or focal neurologic symptoms including headaches, partial or generalized seizures, unilateral or bilateral paresis, hemiplegia, ataxia, visual defects, cognitive impairment, and personality changes (Iacob and Dinca, 2009; Burks et al, 2016; Georgakis et al, 2018). These symptoms persist throughout the course of the disease and worsen following surgical resection, severely limiting day-to-day functions, impacting patients’ quality of life, and even influencing survival outcomes (Martinez et al, 2008; Iacob and Dinca, 2009; Georgakis et al, 2018; Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation